Translational and oncologic significance of tertiary lymphoid structures in pancreatic adenocarcinoma - Gao, Zachary; Azar, Joseph; Zhu, Huili; Williams-Perez, Sophia; Kang, Sung Wook; Marginean, Celia; Rubinstein, Mark P.; Makawita, Shalini; Lee, Hyun-Sung; Camp, E. Ramsay (Frontiers in Immunology, 2024)
Pancreatic adenocarcinoma (PDAC) is an aggressive tumor with poor survival and limited treatment options. PDAC resistance to immunotherapeutic strategies is multifactorial, but partially owed to an immunosuppressive tumor immune microenvironment (TiME). However, the PDAC TiME is heterogeneous and harbors favorable tumor-infiltrating lymphocyte (TIL) populations. Tertiary lymphoid structures (TLS) are organized aggregates of immune cells that develop within non-lymphoid tissue under chronic inflammation in multiple contexts, including cancers. Our current understanding of their role within the PDAC TiME remains limited; TLS are complex structures with multiple anatomic features such as location, density, and maturity that may impact clinical outcomes such as survival and therapy response in PDAC. Similarly, our understanding of methods to manipulate TLS is an actively developing field of research. TLS may function as anti-tumoral immune niches that can be leveraged as a therapeutic strategy to potentiate both existing chemotherapeutic regimens and potentiate future immune-based therapeutic strategies to improve patient outcomes. This review seeks to cover anatomy, relevant features, immune effects, translational significance, and future directions of understanding TLS within the context of PDAC.